Change in Landslide susceptibility over time in the central Himalayan region: A case study of Siddhababa Area - Indu Gyawali,; Birasa Malla,; Khem Nath Poudyal,; Bhim Kumar Dahal, (Advances in Engineering and Technology: An International Journal, 2023)
The susceptibility analysis is common for the study of landslides in the Himalayas, considering different invariant causative factors. This study’s objective is to examine changes in landslide susceptibility within the Siddhababa area by conducting analyses across various time intervals. This area in western Nepal is prone to landslides due to hilly terrain, steep slopes, complex geology, diverse vegetation cover, and extreme weather conditions. This study examines 281 landslides in an area of approximately 257.38 km2, considering 12 causative factors, including three variable factors such as land use, distance to the road, and precipitation, for three different study periods: 2005–2010, 2010–2015, and 2015–2020. For the three study periods, susceptibility analysis, validation, and mapping were performed to prepare susceptibility maps of the study area. The maps were divided into five levels, ranging from very low to very high. The findings show that the high and very high susceptibility levels have increased from 13% to 41% over time, respectively. The changes in the likelihood of landslides are due to both invariant and variable factors such as human activities and climate playing a significant role in altering the susceptibility of the area over time. It is, therefore, essential to comprehend these factors to develop appropriate strategies for mitigating and adapting to the risks posed by landslides and other natural hazards.